Absorption Coefficients of GaN / AlxGa1 – xN Core-Shell Spherical Quantum Dot - D. Abouelaoualim; A. Elkadadra; A. Oueriagli; A. Outzourhit (Журнал нано- та електронної фізики)
The total absorption coefficient in spherical GaN/AlxGa1 – xN core-shell nanodots is theoretically investigated taking into account effective mass approximation. The influence of the nanosystem geometry upon the energy spectrum and transition energy δE associated to interlevel transitions is studied. We found that the energy transitions vary with the core-shell radius, and the peak position of the total absorption coefficient is greatly affected by changing of the shell radius. The possibility of tuning the resonant energies by using the geometric core shell effect of the spatial confinement can be useful in the optoelectronic devices applications. Also we observed that the magnitudes of the total absorption coefficient can be increased significatly compared traditional cases of QD, and the peaks are shifted to the lower energies.